A case study on the Royal Academy of dance syllabus practice in the Steps Dance Studio to create professional dancers. - Bautista, Regina Angelica S.
This case study investigates the professional ballet training of the Steps Dance Studio through its implementation of the RAD syllabus method. It investigates the concepts of the RAD training that is beneficial to training a professional dancer while recognizing the competencies the abilities and skills- achieved within the student to become a professional dancer. It is limited to the RAD practice in the Steps Dance Studio. It covers the concepts of the RAD's training method that is beneficial through the eyes of the founder of the school, its teachers and its students who have gone on to professional companies. Being a case study, it also takes into account my own observation in class and performance.